Early-Warning Warning Systems in Light of the International Debt Crisis - Torsten Amelung; Thorsten Mehltretter (Konjunkturpolitik, Zeitschrift für angewandte Wirtschaftsforschung, 1986)
The paper analyzes and tests various quantitative models to assess the probability of default of sovereign debt, such as scoring models, univariate analysis as well as logit models.The outcomes of the different models are not at a level that they could be used for forecasting or rating. There are basically two reasons for this. On the one hand, the paper focussed on ability-to-pay, while a some defaults are done at a time, when the willingness-to-pay was the underlying problem. On the other, there are some country specific issues that have not been considered in testing the models.
Keywords: C53; C58; F34; G01; H63; 330; Sovereign Debt; Debt Default Models